Assessment by finite element modeling of the interaction of multiple corrosion defects and the effect on failure pressure of corroded pipelines. (15th June 2018) - Sun, Jialin; Cheng, Y. Frank
Highlights: Developed finite element models for assessment of multiple defects on pipelines. Determined the interaction effect of multiple corrosion defects. Determined the effect of multiple corrosion defects on failure pressure of pipelines. Abstract: Determination of the failure pressure of pipelines containing multiple corrosion defects is critical to the integrity and safety of the pipeline infrastructure. In this work, finite element models were developed to determine the failure pressures of X46, X60 and X80 steel pipelines containing multiple corrosion defects with varied geometries and orientations by assessing the mutual interaction of the defects and the effect on pipeline integrity. Generally, the failure pressure of corroded pipelines decreases with the increasing interaction effect between corrosion defects. The interaction effect mainly depends on the mutual orientation of the defects and their geometry and spacing, rather than the steel grade. For longitudinally and circumferentially aligned corrosion defects present on a pipeline, the interaction effect between them does not exist when their spacing is larger than 2.5 Dt and 5.3 t, respectively, where D and t are diameter and wall thickness of the pipeline. As a result, the multiple defects can be assessed individually. Compared to circumferential corrosion defects, the longitudinal defects are associated with a larger spacing where the interaction effect between corrosion defects exists. The circumferential spacing of corrosion defects has a less impact on the failure pressure of corroded pipelines compared with the longitudinal spacing. For pipelines containing overlapped corrosion defects, the failure pressure is lowered, compared to that in the presence of a single top layer defect only. An increase in the depth of either top or bottom layer corrosion defect reduces the failure pressure of the pipeline. The increased length of the defect also increases the interaction effect between the overlapped defects, lowering the failure pressure of the pipeline.